WOOD-BASED PANELS WITH LOW FORMALDEHYDE EMISSION BY COLLAGEN AND KERATIN BIOPOLYMERS (Innovation in Woodworking Industry and Engineering design, 2026)
Urea formaldehyde (UF) adhesives are the most commonly used for wood-based panels, but their main disadvantage is an intensive formaldehyde emission. The aim of the investigation was to reduce the release of formaldehyde from UF bonded wood materials by developing and testing new and more efficient modifiers that bind formaldehyde and form more stable methylene bonds resistant to hydrolysis of the adhesive. Methylol pre-condensate additives with varying ratios of glutaraldehyde and urea modified by fibril proteins based on collagen and keratin were tested. The measurements confirmed the decrease of formaldehyde at all concentrations of methylol pre-condensate compared to the reference sample. Formaldehyde emissions were evaluated from five-layer plywood according to JIS A 1460 (2001): "Building boards. Determination of formaldehyde emission. Desiccator method". The most significant decrease of formaldehyde emission up to 37% was achieved with the application of 5% methylol pre-condensate into UF adhesive standard. The gluing quality has been assessed according to standards EN 314-1 and EN 314-2 and the tested plywood meet the requirements of the standard for Class 1 – suitable for application in the interior.